Appropriate PD-L1 Cutoff Value for Gastric Cancer Immunotherapy: A Systematic Review and Meta-Analysis - Xie, Tong; Zhang, Zhening; Zhang, Xiaotian; Qi, Changsong; Shen, Lin; Peng, Zhi (Frontiers in Oncology, 2021)
Background: Immunotherapy dramatically changed the treatment landscape of gastric cancer in recent years. PD-L1 expression was proposed as a biomarker, however, the treatment strategy according to PD-L1 is still uncertain. Here, we aimed to find the appropriate cut-off value of PD-L1 expression for gastric cancer immunotherapy. Methods: We did a systematic electronic research of prospective clinical trials of gastric cancer immunotherapy across databases. Studies that provided subgroup analysis results stratified by PD-L1 expression were included. Objective response rate (ORR), disease control rate (DCR), hazard ratio (HR) and 95% confidential interval (CI) of progression free survival (PFS) and overall survival (OS) at different PD-L1 cut-off value were extracted. Results: Twelve studies and 6488 patients in total were finally included for pooled analysis. ORR in allover, PD-L1 negative, combined positive score (CPS) ≥1, CPS ≥5 and CPS≥10 population was 10%, 3%, 13%, 20% and 23% respectively. Immune checkpoint inhibitor (ICI) monotherapy failed to show survival advantage in allover and PD-L1 negative patients. Single agent ICI therapy prolonged OS (HR=0.84, 95% CI: 0.74-0.96) but not PFS (HR=1.38, 95% CI: 0.91-2.09) in PD-L1 CPS≥1 patients. For combined immunotherapy, ORR in allover, PD-L1 negative, CPS≥1, CPS ≥5 and CPS≥10 population were 64%, 57%, 48%, 60% and 58% respectively. All-over population could gain survival benefit from combined immunotherapy based on the results from Checkmate-649. OS (HR=0.81, 95% CI: 0.71-0.92) and PFS (HR=0.77, 95% CI: 0.69-0.86) were significantly prolonged in PD-L1 CPS≥1 patients receiving combined immunotherapy. Conclusion: Efficacy and survival advantages improved with PD-L1 CPS. CPS≥1 was the cut-off value for ICI monotherapy to gain survival benefit. Combined immunotherapy prolonged PFS and OS in allover population but need further study to confirm.